Alexander Dmitrievich Kolesnikov (1919–2012): Patriarch of historical science in Siberia - S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность", 2023)
The formation of the Soviet social and political system was accompanied by the internationalization of education and the development of regional historical science. In the course of education, not only the socio-economic history of the region is studied, but also its integration into the state. The purpose of the article is to identify the impact of socio-economic and political processes on the research activities Doctor of Historical Sciences, Professor Kolesnikov A. D. The conclusion is beyond doubt — A. D. Kolesnikov is the creator of a separate direction for the study of settlement and economic development of Siberia in the XVI–XIX centuries. This personality is interesting because his professional formation coincided with the development of the Soviet state: a student in the pre–war years, a soldier who passed two wars, a manager, a witness to the development of Siberia in the 1950s–1980s and a teacher of a higher educational institution. We managed to show how socio-political changes influenced scientific and educational activities.